Clarifying the relationship between pulmonary langerhans cell histiocytosis and Alpha 1 antitrypsin deficiency - Cormac McCarthy; Emmanuelle Bugnet; Amira Benattia; Michael P. Keane; Benoit Vedie; Gwenaël Lorillon; Abdellatif Tazi (Orphanet Journal of Rare Diseases, 2021)
Abstract Pulmonary Langerhans cell histiocytosis (PLCH) is a rare, smoking related, progressive diffuse cystic lung disease that occurs primarily in smokers. The aim of this study was to determine if there was an increase in alpha-1 antitrypsin deficient alleles or phenotypes in a large series of PLCH patients and whether serum alpha-1 antitrypsin levels correlated with markers of disease severity. Fifty PLCH patients, 24 with a diffuse cystic lung pattern and 26 with a typical nodulo-cystic pattern on imaging were included. The mean alpha-1 antitrypsin levels were in normal range for both the population with diffuse cystic lung pattern population (1.39 g/L ± 0.37) and the nodulo-cystic pattern group (1.41 g/L ± 0.21). Deficiency alleles PiZ and PiS were 1% and 2% respectively in the entire study population of 50 patients, demonstrating no increased incidence of alpha-1 antitrypsin deficiency in PLCH. Alpha-1 antitrypsin levels showed no correlation with lung function parameters or extent of cystic lesions on lung computed tomography.